2019
DOI: 10.3390/w11081616
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Rainfall Thresholds for Landslide Occurrence in the Bhutan Himalayas

Abstract: Consistently over the years, particularly during monsoon seasons, landslides and related geohazards in Bhutan are causing enormous damage to human lives, property, and road networks. The determination of thresholds for rainfall triggered landslides is one of the most effective methods to develop an early warning system. Such thresholds are determined using a variety of rainfall parameters and have been successfully calculated for various regions of the world at different scales. Such thresholds can be used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…The temporal probability was calculated using the rainfall threshold determined by Dikshit et al [26] using the Poisson probability model. Readers are referred to [3,39,40] for the detailed explanation on determining the temporal landslide probability.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The temporal probability was calculated using the rainfall threshold determined by Dikshit et al [26] using the Poisson probability model. Readers are referred to [3,39,40] for the detailed explanation on determining the temporal landslide probability.…”
Section: Methodsmentioning
confidence: 99%
“…Gansser [31] described the regional geological setting of the Bhutan Himalayas and characterized the majority of the country as part of the Himalayan Crystalline Complex. The areas that are most prone to landslides are heavily fractured and weathered rocks of phyllite, slate, and schist that contain high amounts of clay [26,27]. The study region has been identified as geologically weak with the presence of several shear zones, including weathered and folded phyllite rocks turning to clay [25].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of precipitation for landslide occurrence can be performed by estimating minimum rainfall conditions, sub surface monitoring, or slope stability analysis. The minimum rainfall conditions, also known as thresholds, can be classified as empirical and physical approaches [40][41][42]. Physical models assess the relationship between rainfall conditions and hydrological conditions of the soil, which affects slope stability.…”
Section: Landslide Forecastingmentioning
confidence: 99%